Survivin as a biological biomarker for diagnosis and therapy - Li, Y; Lu, W; Yang, J; Edwards, M; Jiang, S (Taylor and Francis, 2021)
Introduction: Survivin (SVN) is a member of the inhibitor of apoptosis (IAP) protein family that promotes cellular proliferation and inhibits apoptosis. Overexpression of SVN is associated with autoimmune disease, hyperplasia, and tumors and can be used as a biomarker in these diseases. SVN is widely recognized as a tumor-associated antigen (TAA) and has become an important target for cancer diagnosis and treatment. Areas covered: We reviewed SVN research progress from the PubMed and clinical trials focused on SVN from https://clinicaltrials.gov since 2000 and anticipate future developments in the field. The trials reviewed cover various modalities including diagnostics for early detection and disease progression, small molecule inhibitors of the SVN pathway and immunotherapy targeting SVN epitopes. Expert opinion: The most promising developments involve anti-SVN immunotherapy, with several therapeutic SVN vaccines under evaluation in phase I/II trials. SVN is an important new immune-oncology target that expands the repertoire of individualized combination treatments for cancer.